2015
DOI: 10.1021/acs.joc.5b01356
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Intramolecular Hexadehydro-Diels–Alder Reaction

Abstract: Theoretical analysis of the mechanism of the intramolecular hexadehydro-Diels–Alder (HDDA) reaction, validated against prior and newly measured kinetic data for a number of different tethered yne-diynes, indicates that the reaction proceeds in a highly asynchronous fashion. The rate-determining step is bond formation at the alkyne termini nearest the tether, which involves a transition-state structure exhibiting substantial diradical character. Whether the reaction then continues to close the remaining bond in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 67 publications
3
32
0
Order By: Relevance
“…Results reported in parallel studies by Kuwata and co-workers strongly support this conclusion. 52 Ultimately, the existence of low energy stepwise reactions must be related to the well-known propensity of polyynes to oligomerize and even to explode. 60 In answer to the second question posed above, there is now ample evidence that the intramolecular 1,3-diyne + yne cycloaddition does occur and can lead to o-benzyne intermediates by both concerted and stepwise reaction mechanisms.…”
Section: Scheme 4 Diyne + Yne Cycloadditions and Cycloreversionmentioning
confidence: 99%
“…Results reported in parallel studies by Kuwata and co-workers strongly support this conclusion. 52 Ultimately, the existence of low energy stepwise reactions must be related to the well-known propensity of polyynes to oligomerize and even to explode. 60 In answer to the second question posed above, there is now ample evidence that the intramolecular 1,3-diyne + yne cycloaddition does occur and can lead to o-benzyne intermediates by both concerted and stepwise reaction mechanisms.…”
Section: Scheme 4 Diyne + Yne Cycloadditions and Cycloreversionmentioning
confidence: 99%
“…The open shell singlet and triplet calculation were carried out employing UM06‐2X. In the singlet diradical case wavefunctions of different multiplicity were allowed to mix using the Gaussian keyword “guess = mix”. Triplet contaminations of singlets were accounted for with spin projections and the energy values were corrected using the procedure proposed by Houk and co‐workers .…”
Section: Methodsmentioning
confidence: 99%
“…24 We have observed the same for a series of intra molecular HDDA reactions and found that the (U)B3LYP-D3BJ functional did an excellent job of correlating with our experimentally observed rates. 25 We have not been successful locating transition state structures corresponding to concerted PDDA reactions for 33a–d at this level of theory.…”
mentioning
confidence: 93%